2022
DOI: 10.3389/fcell.2022.933113
|View full text |Cite
|
Sign up to set email alerts
|

Stromal and Immune Cell Dynamics in Tumor Associated Tertiary Lymphoid Structures and Anti-Tumor Immune Responses

Abstract: Tertiary lymphoid structures (TLS) are ectopic lymphoid organs that have been observed in chronic inflammatory conditions including cancer, where they are thought to exert a positive effect on prognosis. Both immune and non-immune cells participate in the genesis of TLS by establishing complex cross-talks requiring both soluble factors and cell-to-cell contact. Several immune cell types, including T follicular helper cells (Tfh), regulatory T cells (Tregs), and myeloid cells, may accumulate in TLS, possibly pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 163 publications
0
7
0
Order By: Relevance
“… 39 40 In addition, Tfh and Treg cells have been reported to act in a complex balance in TLS formation and influence the composition of the neoplastic chronic inflammatory microenvironment. 41 Another study demonstrated that antigen-induced IL-2 production promoted the accumulation of Treg cells, and then contributed to the suppression of Th1-mediated adaptive immune responses. Subsequently, the IL-2-depleted microenvironment transformed some activated CD4 + T cells into Tfh cells, which promoted the formation of TLSs and recruitment of tumor-infiltrating B cells.…”
Section: Discussionmentioning
confidence: 99%
“… 39 40 In addition, Tfh and Treg cells have been reported to act in a complex balance in TLS formation and influence the composition of the neoplastic chronic inflammatory microenvironment. 41 Another study demonstrated that antigen-induced IL-2 production promoted the accumulation of Treg cells, and then contributed to the suppression of Th1-mediated adaptive immune responses. Subsequently, the IL-2-depleted microenvironment transformed some activated CD4 + T cells into Tfh cells, which promoted the formation of TLSs and recruitment of tumor-infiltrating B cells.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in preclinical mouse models show that the interactions between stromal cells and hematopoietic lymphoid tissue-inducer cells (LTi) initiate TLS and SLO development ( 22 , 23 ) ( Figure 1 ). TLS development starts when APCs deliver tumor-associated antigens to adaptive immune cells, resulting in lymphocyte activation and cytokine secretion [e.g., Interleukin-7(IL-7)] ( 24 ).…”
Section: Formation Of Tumor Associated Tertiary Lymphoid Structuresmentioning
confidence: 99%
“…The tumor stroma and lymphatic vessels have been found to undergo extensive remodeling and expansion within the tumor microenvironment. 7 , 49 Non-immune cells associated with the tumor stroma, such as cancer-associated fibroblasts (CAFs), also play many crucial roles in cancer progression, including the exclusion of T cells from the tumor core via extracellular matrix (ECM) remodeling or expression of immunosuppressive molecules. 173 Overexpression of key vascular endothelial growth factors by CAFs and tumor cells promotes the formation of new vessels and enlargement of lymphatic vessels, which enhances tumor growth and dissemination.…”
Section: Defining Interactomes Of Diverse Cell Types Involved In Immu...mentioning
confidence: 99%
“… 6 Immune structures organized to varying degrees, including tertiary lymphoid aggregates (TLAs), mature tertiary lymphoid structures (mTLSs) or ectopic lymphoid structures (ELSs), and immune infiltrates of myeloid origin, can be found modulating the tumor microenvironment across solid tumors. 7 , 8 The location and density of these structures have been proven to have prognostic value, and it is hypothesized that they might contain potential for immunotherapeutic targeting. 9 These immune structures can evolve over time and self-organize into highly ordered structures that resemble lymph nodes, particularly with T cell-rich zones and germinal centers that disseminate humoral immunity.…”
Section: Introductionmentioning
confidence: 99%